Studies on a novel series of acyl ester prodrugs of prostaglandin F2 alpha. - Cheng-Bennett, A (1994)
A novel series of prostaglandin F2 alpha (PGF2 alpha) prodrugs, with acyl ester groups at the 9, 11, and 15 positions, was prepared in order to design clinically acceptable prostaglandins for treating glaucoma. Studies involving isolated esterases and ocular tissue homogenates indicated that 9-acyl esters cannot provide a prodrug since PGF2 alpha would not be formed as a product. In contrast, 11-mono, 15-mono, and 11, 15-diesters were converted to PGF2 alpha in ocular tissues and could, therefore, be considered as prodrugs of PGF2 alpha. Carboxylesterase (CE) appeared critically important for the hydrolytic conversion of those PGF2 alpha prodrugs where the 11 or 15-OH group was esterified and such prodrugs were not substrates for acetylcholinesterase (ACHE) or butyrylcholinesterase (BuCHE). The enzymatic hydrolysis of PGF2 alpha-1-isopropyl ester was also investigated for comparative purposes. This PGF2 alpha prodrug was a good substrate for CE, but was also hydrolysed by BuCHE, albeit at a much slower rate. The most striking feature of the enzymatic hydrolysis of PGF2 alpha-1-isopropyl ester in ocular tissue homogenates was that it was much faster than for prodrugs esterified at the 11 and/or 15 positions. In terms of ocular hypotensive activity, all prodrugs which showed detectable conversion to nascent PGF2 alpha were potent ocular hypotensives. Although no separation of ocular hypotensive and ocular surface hyperaemic effects was apparent for PGF2 alpha-1-isopropyl ester, a temporal separation of these effects was apparent for the novel PGF2 alpha ester series. This difference may reflect an unfavourably rapid conversion of PGF2 alpha-1-isopropyl ester in ocular surface tissues compared with anterior segment tissues.